PEDAGOGY OF UNIVERSAL ARTISTIC THOUGHT - Pavel A. Gagaev (Russian Journal of Education and Psychology)
Background. The article examines the phenomenon of artistic and imaginative thinking and its formation in humans as a pedagogical reality. The problem is as important as it is poorly studied in the literature.